Serum β2-Microglobulin Is Closely Associated With the Recurrence Risk and 3-Month Outcome of Acute Ischemic Stroke - Hu, Fu-yong; Wu, Juncang; Tang, Qiqiang; Zhang, Ji; Chen, Zhengxu; Wang, Xiaoqiang; Liu, Qiuwan; Wang, Juan; Ge, Wei; Qun, Sen (Frontiers in Neurology, 2020)
Background and Purpose: Inflammation plays a significant role in the pathogenesis of acute ischaemic stroke (AIS). The role of β2-microglobulin (β2M) as a potential initiator of the inflammatory response in AIS is unclear. The purpose of this study was to analyse the relationship of serum β2M with the recurrence risk and 3-month outcome of AIS. Methods: A total of 205 patients with AIS were recruited, and their clinical and biochemical characteristics were collected. All patients were followed up for 3 months after stroke onset, and the occurrence of death or major disability at 3 months after onset was the outcome of interest in this study. We evaluated the association of serum β2M levels with National Institute of Health Stroke Scale (NIHSS) scores, modified Rankin Scale (mRS) scores and Essen Stroke Risk Score (ESRS) values in patients with AIS. Then, we used receiver operating curve analysis to calculate the optimal cutoff value for discriminating outcomes in patients with AIS and a binary logistic regression model to evaluate the risk factors for a poor outcome after AIS. Results: Our results showed that serum β2M levels were significantly and positively correlated with ESRS values (r = 0.176, P<0.001) and mRS scores (r = 0.402, P<0.001), but the levels of β2M were not correlated with NIHSS scores (r = 0.080, P = 0.255) or with infarct volume (r = 0.013, P = 0.859). In a further study, we found that 121 patients (59.02%) had poor outcomes. The optimal β2M cutoff to predict the 3-month outcome of AIS in this study was 1.865 mg/l, and β2M was independently associated with a poor outcome at 3 months (OR = 3.325, 95% confidence interval: 1.089~10.148). Conclusions: In conclusion, we inferred that serum β2M was positively associated with the recurrence risk and 3-month outcome of AIS, but it did not appear to be directly related to the severity of AIS or the size of the infarct at admission.